Good human health as a goal of sustainable development of the society: managerial and legal aspect of implementation in Ukraine - Anishchenko, M. A.; Krasnokutskyi, O. V.; Glazunov, V. V.; Bukanov, H. M.; Zharlinska, R.; Аніщенко, Михайло Анатолійович (My University, 2021)
The article examines the category of health as a social value and social benefit, the achievement of which is one of the key priorities of modern Ukrainian society. The paper proves that the category of good health is a goal of sustainable development within the 15 goals of sustainable development formulated by the UN for Ukraine. The article examines the managerial and legal aspect of the formation of public demand for good health as a form of individual and social comfort of Ukrainians. The paper formulates the leading mechanisms for promoting good health as a goal of sustainable development for representatives of different age groups, taking into account gender and age components. The article examines the regional specifics of health and the possibility of implementing management and legal technologies to ensure good health of Ukrainians as a goal of sustainable development of modern Ukrainian society. The paper considers the main problems of achieving sustainable development in Ukraine by increasing the effective functioning of medicine and improving the health of ordinary Ukrainians. The main tasks for achieving the goal of UN sustainable development №3 "Strong health and well-being" are considered. The article considers administrative and legal mechanisms in the field of reducing mortality in road accidents, reducing the number of people suffering from smoking, alcohol, drugs and psychotropic drugs. An important role in the article is given to the issue of measures to reduce mortality of children under 5 years and mothers in labor.
Keywords: good human health; health management; UN sustainable development goals; legal support of the health care system; depopulation of the population